2016
DOI: 10.1002/pc.23962
|View full text |Cite
|
Sign up to set email alerts
|

Properties of polymer composites based on bisphenolAepoxy resins with original/modified steel slag

Abstract: Recently, many inorganic solid wastes have accumulated as a byproduct in several industries and their storage is one of the major problems. Among these wastes, steel slag has attracted attention to utilize with different purposes. In this study, original steel slag (OS) and modified steel slag (MS) were evaluated as a filler to prepare low-cost epoxy composites. The effect of components on the properties of steel slag/ epoxy composites (SECs) was investigated with various analyses and tests. Physicomechanical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 60 publications
1
10
0
Order By: Relevance
“…In the literature, there are several studies on the water sorption of ER composites with bio‐ and solid waste fillers . A comparison between the results obtained in this study and those previously reported in the literature is given in Table .…”
Section: Resultssupporting
confidence: 58%
“…In the literature, there are several studies on the water sorption of ER composites with bio‐ and solid waste fillers . A comparison between the results obtained in this study and those previously reported in the literature is given in Table .…”
Section: Resultssupporting
confidence: 58%
“…Another important residue management is the steel industry wastes (slag or sludge particles), which is mainly composed of Calcium and Iron oxides as well as Silica (SiO 2 ), and has been studied as filler into epoxy resin composites. [ 41,42 ] On the other hand, Dileep and co‐workers [ 43 ] have incorporated silica fume in natural rubber composites and improved modulus in 107% for 20 phr loading, and also increased tear and tensile strength by comparing it to natural rubber gum. The waste, rich in amorphous silica, is obtained from electrofusion process of zirconia but it can also be generated by electric furnaces during the production of silicon.…”
Section: Industrial Residuesmentioning
confidence: 99%
“…Addition of filler materials into the polymeric matrix often performed in the plastics industry. Since most of the reinforcement materials such as TiO 2 , ZnO, clay, CaCO 3 , iron oxides, BaSO 4 , silica, or their mixtures are inexpensive, their addition have the potential to reduce the cost of the materials while improving their properties . In addition, some waste materials could be used in composite preparations.…”
Section: Introductionmentioning
confidence: 99%